Examining the relationship between the use of mobile phones and extension methods in adoption of groundnut farming practices in Northwestern Nigeria - Abu Rimi, Tijjani; Mohamed Haris, Nur Bahiah; Hassan, Salim; Arif Shah, Jasmin; Hamza, Siti Rabaah (Macrothink Institute, 2022)
Adoption of recommended farm practices has been acknowledged to attain food security on groundnut production in Nigeria. Extension agents and other technology developers are now often using various channels of communication, as a means of reaching farmers with improved farm practices to ensure compliance. The aim of the paper is to examine the relationship between the use of mobile phones, individual and group extension methods, technology transfer mechanism in the adoption of improved groundnut farming practices, employing cross-sectional survey in four North-western states of Nigeria. A multi-stage sampling procedure was adopted for interviewing three hundred and thirty-nine farmers. Descriptive and correlation analysis were used to analyze the data. The findings shows that farmers’ had moderate usage levels of mobile phones and individual extension methods, and a high level on group extension methods. Mobile phone, individual and group extension methods had significant relationship with adoption at one percent. While, challenges to the use of mobile phones, individual and group extension methods identified to include; low farmers’ literacy, unstable power supply, poor network, low patronage of extension workers, and also knowledge is restricted to members of the group. It was concluded that the use of mobile phone, individual and group extension methods need to be sustained and improved via government and other stakeholders’ provision of extension agents’, training on utilization of extension methods and mobile phones application for effective technology transfer. Development of farmers’ knowledge on appropriate utilization of mobile phone gadgets will assist them to become receptive and embrace the practices promoted.